2011
DOI: 10.1002/chem.201003376
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Porous Metal–Organic Framework: Structural Transformations of a Guest‐Free MOF Depending on Activation Method and Temperature

Abstract: A doubly interpenetrating porous metal-organic framework (SNU-77) has been synthesized from the solvothermal reaction of the extended carboxylic acid tris(4'-carboxybiphenyl)amine (H(3)TCBPA) and Zn(NO(3))(2)⋅6H(2)O in N,N-dimethylacetamide (DMA). SNU-77 undergoes single-crystal-to-single-crystal transformations during various activation processes, such as room-temperature evacuation, supercritical CO(2) drying, and high temperature evacuation, to afford SNU-77R, SNU-77S, and SNU-77H, respectively. These guest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…ing Information), similarly to the case of SNU-77 S. [21] The powder X-ray diffraction patterns indicate that the framework structure of SNU-150' is similar to that of SNU-150 ( Figure 3).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…ing Information), similarly to the case of SNU-77 S. [21] The powder X-ray diffraction patterns indicate that the framework structure of SNU-150' is similar to that of SNU-150 ( Figure 3).…”
Section: Resultsmentioning
confidence: 53%
“…It is quite well recognized that charged frameworks show superior gas sorption properties to neutral ones. [18,[28][29][30] When the gas adsorption properties of SNU-150' are compared with those of SNU-77 S, [21] which also has PdF 2 topology, it is found that SNU-150' adsorbs much smaller amounts of N 2 and H 2 gases at 77 K and 1 atm, as well as a smaller amount of CO 2 gas at 195 K and 1 atm. This must be attributed to the significantly smaller surface area (1852 m 2 g À1 ) of SNU-150' than that (3670 m 2 g À1 ) of SNU-77 S. When the gas adsorption properties of SNU-151' are compared with those of SNU-100', which has an anionic framework with diethA C H T U N G T R E N N U N G yl-A C H T U N G T R E N N U N G ammonium cations, it is observed that SNU-151' is superior to SNU-100'.…”
Section: Gas Sorption Propertiesmentioning
confidence: 99%
“…[5] Large variations in the resulting sorption capacity were observed for these three methods.I naseparate study Park and co-workers investigated the effect of activation methods on the fine structure of SNU-77, also at hree-dimensional Zn carboxylate. [6] Yang et al were also able to optimise the sorption capacity of Cu-BTC by solvent exchange with various solvents prior to activation. [7] In general, however,d etailed structural investigations of the effect of solvent-mediated activation are limited.…”
mentioning
confidence: 99%
“…Our best estimate of the 0 K H 2 adsorption enthalpy, ∆H bind (0 K), was −12.4 kJ.mol −1 , 20 within 2 kJ.mol −1 of the experimentally measured ∆H ads of H 2 to bare metal sites. 21 In this paper we extend our 0 K calculations to finite temperature; in the long term, room temperature H 2 storage is required if H 2 is to become a viable alternative to fossil fuels in vehicles. Moreover, the experimental characterisation of putative H 2 storage materials typically takes place between 77 and 98 K. 22 Although quantum effects become less important as temperature increases, H 2 is known to exhibit quantum behaviour at ambient temperature, 17,19 and thus a quantum rather than classical formalism is required.…”
Section: Introductionmentioning
confidence: 94%